Pendidikan Berbasis Entrepreneurship: (Persepektif Tinjauan Sosiologi Pendidikan) - Hosaini Hosaini (Kependidikan Islam Fakultas Agama Islam, 2018)
Education is the biggest asset of a nation with the aim of contributing in the form of skills to children not to awkward facing the future. While the funcion of education is to form characteristic and the child morality of nation in order to have integrity with high morals and love the nation. So that, the education is the most veluable treasure belonging to nation. To improve the quality of education is not easy as flipping a hand. There are a few things that need to be made a foothold. One of them is education incurred the competen as well as meet the learning facilities. That is one of the things that needs to be taken by the managers of education.To complete it needs the cost of expensive, so it is usually a problem for managers of eduacion. Because, if they rely solely on education budget from the government and the students, then it will be difficult to improve the quality of education. While the things that should be financed by the institution’s of education is not only the supplies of education, but also pay the employees and maintenance of the school. Moreover, the institution of education that a public school to meet the needs is not easy. So, to improve the quaity of education as well as spend the treasures of institution including the treasure of edutator.There are several stages that should be applied in developing enterpreurship in the world of education, so that it walk well, those are; identify the aim that will be achieved, ready to accept the risks that will be accepteble to both the power of money as well as time, prepare the ability to make the plan of organizing, coordinating and implementing programs, committed to work hard all the time and believe to be successful on all work done, develop good relationship with costumer, educational personnel, parent, community, social institutions, the government and the corporate world that impact educational activities, receiving the benefit and responsibility for the successes dan failures.